The Application of Qur'anic Discovery Learning Model in Nurturing the “Scientific Attitude” Character of Fifth Grade Students in Elementary School - Masithoh, Dewi; Misor, Amdul (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
Technological developments exert a profound influence on all sectors. Education plays a key role in shaping scientific attitudes in elementary school students. This study aims to describe the implementation of the Qur'ani discovery learning model in training the scientific attitude character of grade V students in elementary schools. The present study adopts a qualitative research approach, specifically a case study design. The research was conducted from July to December 2022. The research subjects were fifth-grade teachers and students at SDIT Lukman Al Hakim International Yogyakarta. The data collection techniques employed included interviews, observations, and documentation. The Lankshear and Knobel model was utilised to analyse the data. The validity of the data was established through the utilisation of subject triangulation and method triangulation techniques. The findings revealed that the implementation of the Qur'ani discovery learning model in training students' scientific attitudes in elementary schools consists of a 7M learning cycle, including admiring, appreciating, researching, realising, realising, collaborating, actualising, and giving. The study experience will be more meaningful if it is carried out with various learning activities both inside and outside the classroom, so that the character of scientific attitudes can be formed in primary school students.